(untitled) (Journal of Hama University, 2024)
In this research, a study was conducted to determine the effect of recycled aggregates on the mechanical properties of concrete produced from it such as compressive strength, modulus of elasticity and tensile strength. An experimental and analytical study was conducted on the behavior of reinforced concrete beams subject to torsion in all cases of complete and partial replacement according to the following ratios (0%-25%-50%-75%-100%).The current study showed that the studied mechanical properties were influenced by the presence of recycled aggregates, and the experimental results showed a decrease in the cylindrical resistance to pressure by a rate ranging between (3.8%-18.4%), and a decrease in the elastic modulus Ec by a rate ranging between (10.3%-26.9%), and the tensile strength by splitting decreased by a rate ranging between (15.4%-25.8%), with an increase of Reconstituted aggregates compared with reference samples composed of (R0) natural aggregates. An experimental study was conducted by applying the torsional torque on reinforced concrete beams composed of natural aggregates and recycled aggregates of groups (R0,R25,R50,R75,R100) and the results showed that the average maximum torsional torque of three beams of each group decreased by (8.9%-13.1%-20.4%-26.7%) compared to reinforced concrete beams composed of natural aggregates (R0). The analytical results gave a good agreement with the experimental results in terms of the distribution and shape of the cracks, and the results showed that the percentage difference in the maximum torsion moment between the experimental and the analytical ranged between (4%-5.7%), and the difference in the angle of torsion ranged between (4.8%-11.6%) for all groups.